How butterflies keep their cool: Physical and ecological traits influence thermoregulatory ability and population trends. Issue 11 (23rd September 2020) - Bladon, Andrew J.; Lewis, Matthew; Bladon, Eleanor K.; Buckton, Sam J.; Corbett, Stuart; Ewing, Steven R.; Hayes, Matthew P.; Hitchcock, Gwen E.; Knock, Richard; Lucas, Colin; McVeigh, Adam; Menéndez, Rosa; et al.
Abstract: Understanding which factors influence the ability of individuals to respond to changing temperatures is fundamental to species conservation under climate change. We investigated how a community of butterflies responded to fine‐scale changes in air temperature, and whether species‐specific responses were predicted by ecological or morphological traits. Using data collected across a UK reserve network, we investigated the ability of 29 butterfly species to buffer thoracic temperature against changes in air temperature. First, we tested whether differences were attributable to taxonomic family, morphology or habitat association. We then investigated the relative importance of two buffering mechanisms: behavioural thermoregulation versus fine‐scale microclimate selection. Finally, we tested whether species' responses to changing temperatures predicted their population trends from a UK‐wide dataset. We found significant interspecific variation in buffering ability, which varied between families and increased with wing length. We also found interspecific differences in the relative importance of the two buffering mechanisms, with species relying on microclimate selection suffering larger population declines over the last 40 years than those that could alter their temperature behaviourally. Our results highlight the importance of understanding how different species respond to fine‐scale temperature variation, and the value of taking microclimate into account in conservation management to ensure favourable conditions are maintained for temperature‐sensitive species. Abstract : The ability of individual animals to respond to local temperature changes will determine how species respond to climate change. The authors found marked differences in the ability of 29 butterfly species to 'buffer' their body temperature against changes in air temperature, and show that species' buffering mechanisms predict their population trend.